2003
DOI: 10.1167/iovs.02-1204
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Protects the Inner Retina from Apoptosis and Ischemia-Induced Loss of Vesl-1L/Homer 1c Immunoreactive Synaptic Connections

Abstract: Immunoreactivity for V-1L can be used as a synaptic marker for early changes before more severe neurodegenerative events. The present results suggest that estrogen protects neurons in the GCL including RGCs from both apoptosis and early changes in synaptic connections associated with ischemia and potentially preceding apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
71
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 76 publications
(77 citation statements)
references
References 53 publications
6
71
0
Order By: Relevance
“…Further evidence for a link between hormonal status and risk of microvascular complications associated with type 1 diabetes was provided by a study showing that women with diabetic retinopathy and nephropathy undergo menopause at an earlier age [37]. Several experimental studies have demonstrated a renoprotective role for exogenous oestrogens in models of type 1 diabetic retinopathy and nephropathy [38][39][40]. It is possible that early onset of diabetes impairs the ovarian production of oestrogen, thus becoming permissive for the development of organ complications later in life.…”
Section: Discussionmentioning
confidence: 99%
“…Further evidence for a link between hormonal status and risk of microvascular complications associated with type 1 diabetes was provided by a study showing that women with diabetic retinopathy and nephropathy undergo menopause at an earlier age [37]. Several experimental studies have demonstrated a renoprotective role for exogenous oestrogens in models of type 1 diabetic retinopathy and nephropathy [38][39][40]. It is possible that early onset of diabetes impairs the ovarian production of oestrogen, thus becoming permissive for the development of organ complications later in life.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these limbo-corticostriatal structures, all three Homer isoforms are located within cerebellum [106] and while the expression of Homer3 within the olfactory bulbs is developmentally down-regulated, the expression of both Homer1 and Homer2 isoforms persist throughout development [106]. Within neurons, Homer proteins are localized predominantly in the soma and apical dendrites [102,105,144,158]. At a subcellular level, Homer proteins are enriched within the postsynaptic density (PSD) fraction, but are also present in the crude nuclear, synaptosomal and microsomal fractions [105,144].…”
Section: Homers Are Regulated Within Addiction-related Neural Circuitmentioning
confidence: 99%
“…Specifically, we have previously described loss of Vesl-1L/Homer-1c as biomarker for synaptic changes after injury in the retina (Kaja et al 2003), and experimental down-regulation of Homer1b/c has been shown to attenuate glutamate-mediated toxicity in cortical neurons in vitro (Chen et al 2012).…”
Section: Introductionmentioning
confidence: 99%